2021
DOI: 10.1109/access.2021.3130550
|View full text |Cite
|
Sign up to set email alerts
|

Practical Model for Optimal Carbon Control With Distributed Energy Resources

Abstract: The generation, consumption, and transmission of distributed energy produced by a microgrid are becoming increasingly important topics in scientific research. As a power source that partly relies on renewable energy, microgrids play a vital role in the global energy network. In this study, the underlying principles and management techniques of microgrids are introduced. Microgrids can reduce the carbon footprint of the energy production process. This study also provides insight into how decision-makers can con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Studies have also been performed on power enterprise management (for example, Refs. [30,46] and suggestions for improving the efficiency of power management), electricity carbon market (for example, Refs. [30,47], which also mention the linkage trading scheme of the carbon market), virtual power plant, new energy storage, new two-way interaction of load, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also been performed on power enterprise management (for example, Refs. [30,46] and suggestions for improving the efficiency of power management), electricity carbon market (for example, Refs. [30,47], which also mention the linkage trading scheme of the carbon market), virtual power plant, new energy storage, new two-way interaction of load, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[30,46] and suggestions for improving the efficiency of power management), electricity carbon market (for example, Refs. [30,47], which also mention the linkage trading scheme of the carbon market), virtual power plant, new energy storage, new two-way interaction of load, etc. In the future, it will also play an important role in the field of ecological energy, cross-chain transparent power systems, power market trust mechanisms, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the analysis of energy trading and distributed energy, the Ref. (Su et al, 2021) showed that energy blockchain technology is a valuable asset for expanding the use of clean energy, reducing carbon emissions in power, and optimizing power management in a microgrid.…”
Section: Lower Carbon Pollution Emissionsmentioning
confidence: 99%
“…et,CD is the carbon emission derived from both the DER and the power utility. Follow up on these formulae, one may derive the value dependency law [35]. In the microgrid economics and carbon emission calculation model, the first row of the matrix indicates that the power demand of the load the power demand of the load in a microgrid must be met in total by the current level of energy production, available stored energy, and energy provided by an external power grid.…”
Section: Guidelines For Manuscript Preparation a Characteristics Of C...mentioning
confidence: 99%